Pemeriksaan Lutut dan Sosialisasi Latihan Kekuatan dan Stabilitas Lutut untuk Mencegah Cedera ACL dan Osteoarthritis - Adhitya, I Putu Gde Surya; Winaya, I Made Niko; Saraswati, Putu Ayu Sita; Thanaya, Sayu Aryantari Putri; Suputri, Ni Wayan Bintang Mida; Wijaya, Gede Wahyu Pratama; Kurniawati, Ida (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Elderly individuals undergo various changes in their social, mental, physical, and body functional aspects. Workers in the agricultural sector, especially in areas like Takmung Village, frequently engage in activities that require prolonged use of the knees. This can increase the risk of knee osteoarthritis and injuries, especially during actions such as kneeling, squatting, or standing for extended periods while working. As a result, many farmers in Takmung Village experience discomfort and pain in their knees. Therefore, the community service activity aims to identify the characteristics of the elderly and enhance knowledge and understanding related to the prevention and management of ACL injuries and knee osteoarthritis. The community service activity was conducted from June to August 2023 at the Banjar Lepang Meeting Hall in Takmung Village, Klungkung Regency, and was attended by 54 productive elderly individuals. The activities began with planning, permit management, coordination meetings, training preparation, socialization implementation, health examinations, and pre-test and post-test evaluations. Out of the 54 elderly participants, 53 showed increased knowledge through pre-test and post-test assessments, while only one experienced a decrease. The impact of the socialization activities resulted in improved knowledge among the elderly regarding methods to prevent ACL injuries and knee osteoarthritis. They also gained awareness of suitable physical exercises to prevent and alleviate symptoms associated with ACL injuries and knee osteoarthritis conditions.